Respuesta :

Answer:

[tex]f^{-1}(x)=\frac{1}{8}(x-4)^{3}[/tex]

Step-by-step explanation:

Given function is,

f(x) = [tex]\sqrt[3]{8x}+4[/tex]

To find the inverse of this function,

Rewrite the function as a equation,

y = [tex]\sqrt[3]{8x}+4[/tex]

Interchange x by y and y by x,

x = [tex]\sqrt[3]{8y}+4[/tex]

Now solve this equation for y,

x - 4 = [tex]\sqrt[3]{8y}[/tex]

(x - 4)³ = [tex](\sqrt[3]{8y})^3[/tex]

(x - 4)³ = 8y

y = [tex]\frac{1}{8}(x-4)^{3}[/tex]

Now convert the equation into function,

[tex]f^{-1}(x)=\frac{1}{8}(x-4)^{3}[/tex]